The Rise of Cloud Computing and the Importance of IaC - Amandeep Singh Saini, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Infrastructure as Code (IaC) has emerged as a transformative approach in cloud computing, revolutionizing how organizations manage and deploy their infrastructure. By treating infrastructure configurations as software code, IaC enables automated, consistent, and scalable deployment processes across multiple cloud environments. The shift from traditional manual infrastructure management to automated IaC practices has significantly enhanced operational efficiency, reduced human errors, and strengthened security postures. Organizations leveraging IaC benefit from rapid deployment capabilities, standardized management practices, and improved resource optimization. The integration of IaC with DevOps workflows has further accelerated digital transformation initiatives, enabling seamless collaboration between development and operations teams. The adoption of security-first IaC practices has strengthened compliance adherence and reduced vulnerability exposure through automated security controls and continuous monitoring. As the technology landscape evolves, the incorporation of artificial intelligence and machine learning capabilities in IaC workflows promises to deliver enhanced infrastructure optimization, predictive analytics, and automated decision-making, positioning IaC as a cornerstone of modern cloud infrastructure management.
Keywords: Infrastructure as Code; Cloud Computing; DevOps Integration; Multi-cloud Management; Security Automation